The influence of celebrity endorser and brand image on consumer purchasing decisions of Rabbani Stores in Pekanbaru City - Novi Andryani; Mandataris (Institute of Computer Science (IOCS), 2023)
This study aims to determine whether celebrity endorsers and brand image influence purchasing decisions. The research method used is quantitative, using primary data and secondary data. Primary data were obtained from respondents collected through questionnaires. The sample amounted to 88 respondents using purposive sampling from a population of 770 consumers who had made a purchase. The measurement scale uses the Likert scale. Data analysis includes validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, simple linear regression analysis, multiple linear analysis, determination coefficient test, t-test, and f test using SPSS 26. The results showed (1) there is a significant influence of celebrity endorsers on the purchasing decisions of Rabbani Store consumers in Pekanbaru City.